1985
DOI: 10.1203/00006450-198511000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indomethacin upon Cerebral Hemodynamics of Newborn Pigs

Abstract: Treatment of unanesthetized newborn pigs with indomethacin trihydrate (5 +/- 1 mg/kg, intravenous) decreased cerebral blood flow uniformly throughout the brain by 18-28% without changing cardiac output, arterial pressure, or arterial blood gases and pH. Breathing 10% O2, 9% CO2 with the balance N2 (hypoxia/hypercapnia) caused cerebral blood flow to increase from 102 +/- 12 to 218 +/- 19 ml/100 g . min. Intravenous administration of indomethacin during hypoxia/hypercapnia caused a uniform decrease in cerebral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 0 publications
2
49
0
Order By: Relevance
“…To our knowledge, this ef fect of IND on the cerebrovascular response to the mixed gases has not been previously reported for adult animals. In unanesthetized neonatal piglets, Leffler et al (1985) found that the CBF increased if the animals breathed a hypoxic/hypercapnic gas mixture. However, after administering IND the CBF decreased to levels comparable to those mea sured while the animals breathed room air.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this ef fect of IND on the cerebrovascular response to the mixed gases has not been previously reported for adult animals. In unanesthetized neonatal piglets, Leffler et al (1985) found that the CBF increased if the animals breathed a hypoxic/hypercapnic gas mixture. However, after administering IND the CBF decreased to levels comparable to those mea sured while the animals breathed room air.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The endothelium is a major source of PGI 2 which is generated in response to a number of different stimuli including vascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelium-derived PGI 2 is an essential molecule responsible for preservation of cerebrovascular homeostasis under pathological conditions when blood vessels are exposed to injury induced by stroke, inflammation, and brain trauma. [1][2][3]6,7,43,44 Indeed, PGI 2 has been identified as a major protective product of arachidonic acid metabolism within the vasculature. 6 In the cerebral circulation, elevated production of PGI 2 in response to vascular injury is designed to prevent aggregation of platelets, to preserve blood flow, and to inhibit aberrant remodeling of injured vascular wall.…”
mentioning
confidence: 99%
“…11 Similarly, by decreasing fetal cerebral blood flow, AI may cause fetal central nervous system hypoperfusion injury resulting in PVL. 12 The profound effects of indomethacin on platelet and neutrophil function may lead to increased incidence of IVH and sepsis. 13 AI is associated with in utero constriction of the fetal ductus arteriosus.…”
Section: Introductionmentioning
confidence: 99%